COMPLICAÇÕES DA COVID-19 EM GESTANTES (Movimenta (ISSN 1984-4298), 2022)
Introduction: In 2019, an infectious disease known as COVID-19 emerged, which causes respiratory failure and pneumonia in affected individuals, with a high mortality rate. The profile of more severely compromised individuals has changed over time and pregnant women are now included in this scenario because they are more susceptible to respiratory microorganisms. Objective: Check the main complications that COVID-19 can cause in pregnant. Materials and methods: Integrative review in the VHL (Virtual Health Library) and Pubmed (United States National Library of Medicine) databases, from 2019 to 2021, using the PICO strategy to elaborate the guiding question of the research. Results: 1,161 articles were found, which after applying the inclusion and exclusion criteria, 9 are selected for the analysis of their respective aspects: title, objective, methods and/or instruments used and the results of each article. Conclusion: Covid-19 triggered various repercussions/complications in the maternal and/or fetal organism, such as: preeclampsia, premature birth, premature rupture of membranes, thrombotic events and emergency cesarean, thus causing deleterious effects compromising health and generating negative impacts. Keywords: Risk pregnant women, Pregnancy Complications, Covid-19.